2005
DOI: 10.1074/jbc.m408215200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Annexin II-S100A10 Complex in the Formation of E-cadherin-based Adherens Junctions in Madin-Darby Canine Kidney Cells

Abstract: E-cadherin and nectins are major cell-cell adhesion molecules at adherens junctions (AJs) in epithelial cells. When Madin-Darby canine kidney (MDCK) cells stably expressing nectin-1 (nectin-1-MDCK cells) are cultured at normal Ca(2+), E-cadherin and nectin-1 are concentrated at the cell-cell contact sites. When these cells are cultured at low Ca(2+), E-cadherin disappears from the cell-cell contact sites, but nectin-1 persists there. When these cells are re-cultured at normal Ca(2+), E-cadherin is recruited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 46 publications
1
51
0
1
Order By: Relevance
“…It is possible that, by coordinating with the tiny amount of residual PAR-3 in PAR-3 kd cells, overexpressed Girdin can overcome the polarity defects caused by PAR-3 knockdown. Several early studies have demonstrated that increased synthesis of regulatory proteins is required for the establishment of cell-cell junctions (Griepp et al, 1983;Sang et al, 1980;Yamada et al, 2005). Our findings provide additional insight into this mechanism.…”
Section: Regulation Of Girdin Transcription By the Par-3 Cell Polaritmentioning
confidence: 50%
“…It is possible that, by coordinating with the tiny amount of residual PAR-3 in PAR-3 kd cells, overexpressed Girdin can overcome the polarity defects caused by PAR-3 knockdown. Several early studies have demonstrated that increased synthesis of regulatory proteins is required for the establishment of cell-cell junctions (Griepp et al, 1983;Sang et al, 1980;Yamada et al, 2005). Our findings provide additional insight into this mechanism.…”
Section: Regulation Of Girdin Transcription By the Par-3 Cell Polaritmentioning
confidence: 50%
“…In epithelial cell layers, annexin A2 was shown to regulate cell spreading and wound closure in line with an increased expression of annexin A2 in migrating versus stationery epithelial cells (Babbin et al, 2007). Furthermore, in endothelial cells the reduction of annexin A2 plasma membrane levels by cholesterol depletion or RNAi inhibited the recruitment of E-cadherin and thereby cell contact formation, which itself negatively regulates migration (Yamada et al, 2005). It will be interesting to learn whether the effect of annexin A2 on cell contact formation is also regulated by its tyrosine phosphorylation, which has been established here as a molecular switch transforming cellular actin from a stationary to a more migratory phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…Nectins also regulate cytoskeletal dynamics via F-actin binding proteins that interact directly with nectin [e.g., afadin, ␣-catenin, ␣-actinin, vinculin, annexin II and IQGAP Miyoshi and Takai, 2007)] (Fig. 1), and establishment of nectin-based adherens junctions required annexin II and IQGAP in MDCK cells (Katata et al, 2003;Yamada et al, 2005aYamada et al, , 2006a. Furthermore, nectin-afadin can also recruit tight junction proteins such as claudin, occludin, JAM-A, and ZO-1 to the junctional complex (Yokoyama et al, 2001;Fukuhara et al, 2002;Takai and Nakanishi, 2003;Sato et al, 2006), suggesting the existence of cross talk between different junction types.…”
Section: A Cell-cell Actin-based Adherens Junctionsmentioning
confidence: 99%